Flexible Entry into 3-Arylpent-2-enedioic Acids via Heck–Matsuda Arylation of Dimethyl Glutaconate with Arenediazonium Tosylates - Dar’in, Dmitry; Kantin, Grigory; Bakulina, Olga; Žalubovskis, Raivis; Krasavin, Mikhail (Synthesis, 2019)
For the preparation of compound libraries of Michael acceptors with tunable reactivity toward nuclophilic selenocysteine residue of thioredoxin reductase, a range of 3-arylglutaconic acids were required. The existing methods at the time had limited scope or involved several steps. A hitherto undescribed protocol for direct palladium(II) acetate-catalyzed arylation of glutaconic acid dimethyl ester at position 3 has been developed with a diverse set of arenediazonium tosylates followed by hydrolysis. This generally good-yielding two-step sequence displayed a propensity to deliver E-configured coupling products while compounds mostly featured in the literature were predominantly Z-configured. The possibility for preparing a library of 4-arylpyridine-2,6(1H,3H)-diones has been exemplified.
Keywords: arylpent-2-enedioic acids; glutaconic acid; diazonium tosylate; Pd-catalyzed coupling; regiospecificity; ester hydrolysis; imide synthesis